ISOLATION AND CHARACTERIZATION OF A NOVEL ANTIMICROBIAL COMPOUND FROM SUB-AERIAL CYANOBACTERIUM Fischerella sp., ISOLATED FROM BUILDING FACADES (Applied Biological Research, 2023)
This work was aimed at to extract a novel antimicrobial compound,  especially against certain human pathogens, from a sub-aerial  cyanobacterium Fischerella sp., isolated from the building facades of  Bhubaneswar, Odisha (India). The antimicrobial activity was determined  in different solvents and aqueous extracts using agar well diffusion  method which were purified using column chromatography and TLC  (twice), followed by direct bioautography, MIC, cytotoxicity and was  characterized using UV-Vis, FTIR and LC-MS spectroscopic methods.  The lowest MIC value (0.312 and 0.625 mg mL-1) was depicted by the acetone extracted single compound against Escherichia coli and Candida albicans. The bioautography and spectroscopic analysis revealed the  compound to be an alkaloid which was identified as pentaphenyl  ferrocene carboxamide and found to be non-toxic against Catla thymus  macrophage and Mus musculus up to 72 h. The cyanobacterium was  identified as Fischerella sp. (accession No. MN593556) through 16S rRNA  technique. The compound has potential for use as a therapeutic drug.
Keywords: Antimicrobial; cytotoxicity; Fischerella sP; natural bioactive compound; spectroscopic analysis